1971
DOI: 10.1159/000301861
|View full text |Cite
|
Sign up to set email alerts
|

Use of Androgen Antagonists and Antiandrogens in Studies on Sex Differentiation

Abstract: his review paper, including some unpublished results, summarizes some of the effects on sex differentiation in male fetuses of drugs which inhibit enzymes involved in steroid hormone synesis or of antiandrogens, especially cyproterone acetate. The former have only very slight effects on morphological sex differentiation. Cyproterone acetate is a very potent antimasculine agent in several species (rabbit, dog and probably others); in other species (rat, guinea pig, calf) the results obtained so far are at varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The indifferent stage of genital development ends after approximately 8–9 weeks of gestation when wholemount analysis reveals the first macroscopic signs of divergent male and female differential development. This is best seen in Figure 2 where the presence or absence of testosterone and Müllerian inhibiting substance synthesized in the fetal testis initiates male and female differentiation (Behringer et al, 1994; Jost, 1971; 1972). In males, prostatic buds appear at ~10 weeks of gestation (Cunha et al, 2018b), the Wolffian ducts are stabilized and the Müllerian ducts regress.…”
Section: Discussionmentioning
confidence: 97%
“…The indifferent stage of genital development ends after approximately 8–9 weeks of gestation when wholemount analysis reveals the first macroscopic signs of divergent male and female differential development. This is best seen in Figure 2 where the presence or absence of testosterone and Müllerian inhibiting substance synthesized in the fetal testis initiates male and female differentiation (Behringer et al, 1994; Jost, 1971; 1972). In males, prostatic buds appear at ~10 weeks of gestation (Cunha et al, 2018b), the Wolffian ducts are stabilized and the Müllerian ducts regress.…”
Section: Discussionmentioning
confidence: 97%
“…Rats and rabbits show a similar growth of gubernacular cones. The animals differ, however, with respect to the completeness (rabbits more than rats) with which development of the androgen-dependent Wolffian duct derivatives can be prevented through anti-androgen (Jost, 1971172).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, AMH signals the prenatal regression of the Müllerian ducts in the fetus. AMH and testosterone act synergistically to suppress the development of Müllerian ducts and promote the development of Wolffian ducts in male embryos, whereas in the absence of these two hormones the Müllerian ducts develop into female genitalia [ 17 , 18 ]. Our study confirmed a correlation between the prevalence of Müllerian duct anomalies due to abnormal organogenesis of the uterus and high AMH levels in patients with PCOS, inferring that the association between PCOS and some types of Müllerian duct anomalies, such as unicornuate uterus, could be explained by certain developmental defects that contribute to both PCOS and Müllerian duct anomalies.…”
Section: Discussionmentioning
confidence: 99%